SMART PARENTING IN IMPROVING STUDENTS’ SPIRITUAL INTELLIGENCE IN PESANTREN-BASED MADRASAHS - Zamroni Zamroni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
Smart parenting is a pattern of children's education, that parents or caregivers accompany and guide the growth of children towards the creation of a golden generation in accordance with the expectations of all parties. The focus of this research lies in the effort to implement smart parenting in improving the spiritual intelligence of students at MTs Nabil Husein Samarinda and MTs Al Mujahidin Samarinda. This research used a qualitative approach with case study. The results show that the implementation of smart parenting in improving the spiritual intelligence of students at MTs Nabil Husein Samarinda and MTs Al Mujahidin Samarinda is carried out in a planned and systematic manner. The steps taken to implement smart parenting were; 1) planning smart parenting activities designed by the madrasah by involving all existing components, 2) implementng smart parenting as a form of implementation of the existing planning design, and 3) evaluating smart parenting activities with the principles of openness, objectivity and based on continuous improvement. The results of these activities appear on the students’ discipline behavior, adherence to existing regulations and responsibility.